X chromosomes show relaxed selection and complete somatic dosage compensation across Timema stick insect species. (7th August 2022) - Parker, Darren J.; Jaron, Kamil S.; Dumas, Zoé; Robinson‐Rechavi, Marc; Schwander, Tanja
Abstract: Sex chromosomes have evolved repeatedly across the tree of life. As they are present in different copy numbers in males and females, they are expected to experience different selection pressures than the autosomes, with consequences including a faster rate of evolution, increased accumulation of sexually antagonistic alleles and the evolution of dosage compensation. Whether these consequences are general or linked to idiosyncrasies of specific taxa is not clear as relatively few taxa have been studied thus far. Here, we use whole‐genome sequencing to identify and characterize the evolution of the X chromosome in five species of Timema stick insects with XX:X0 sex determination. The X chromosome had a similar size (approximately 12% of the genome) and gene content across all five species, suggesting that the X chromosome originated prior to the diversification of the genus. Genes on the X showed evidence of relaxed selection (elevated dN/dS) and a slower evolutionary rate (dN + dS) than genes on the autosomes, likely due to sex‐biased mutation rates. Genes on the X also showed almost complete dosage compensation in somatic tissues (heads and legs), but dosage compensation was absent in the reproductive tracts. Contrary to prediction, sex‐biased genes showed little enrichment on the X, suggesting that the advantage X‐linkage provides to the accumulation of sexually antagonistic alleles is weak. Overall, we found the consequences of X‐linkage on gene sequences and expression to be similar across Timema species, showing the characteristics of the X chromosome are surprisingly consistent over 30 million years of evolution.